Massive traumatic abdominal wall hernia in pediatric multitrauma in Australia: a case report - Sarah Douglas-Seidl; Camille Wu (Journal of Trauma and Injury)
Traumatic abdominal wall hernia is a rare presentation, most commonly reported in the context of motor vehicle accidents and associated with blunt abdominal injuries and handlebar injuries in the pediatric population. A 13-year-old boy presented with multiple traumatic injuries and hemodynamic instability after a high-speed motor vehicle accident. His injuries consisted of massive traumatic abdominal wall hernia (grade 4) with bowel injury and perforation, blunt aortic injury, a Chance fracture, hemopneumothorax, and a humeral shaft fracture. Initial surgical management included partial resection of the terminal ileum, sigmoid colon, and descending colon. Laparostomy was managed with negative pressure wound therapy. The patient underwent skin-only primary closure of the abdominal wall and required multiple returns to theatre for debridement, dressing changes, and repair of other injuries. Various surgical management options for abdominal wall closure were considered. In total, he underwent 36 procedures. The multiple injuries had competing management aims, which required close collaboration between specialist clinicians to form an individualized management plan. The severity and complexity of this injury was of a scale not previously experienced by many clinicians and benefited from intrahospital and interhospital specialist collaboration. The ideal aim of primary surgical repair was not possible in this case of a giant abdominal wall defect.